A vanadium-free hydrogen storage alloy and preparation method thereof

By optimizing the proportion of metal components and the rapid quenching technology of the melt, the alloy structure is converted, and the problem of the existing hydrogen deposits and the expensive ingredients in the process of crystal cells and raw materials in the process of hydrogen. Hydrogen storage alloy.

CN116162837BActive Publication Date: 2025-01-28GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310215638.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-08
Publication Date
2025-01-28
Estimated Expiration
2043-03-08

AI Technical Summary

Technical Problem

The existing hydrogen storage alloys have the problem of large unit cell volume expansion during the hydrogen absorption and release cycle, and vanadium as the raw material for hydrogen storage alloys has the disadvantage of being expensive, making it difficult to meet the needs of high capacity and low cost.

Method used

By optimizing the proportion of metal TI, CR, and M, and using melting fast quenching technology, regulating the crystal structure of the alloy, transforming from Laves phase of cast -in alloy to BCC phase, obtaining the hydrogen -free hydrogen storage hydrogen storage hydrogen storage performance alloy.

Benefits of technology

It improves the capacity and hydrogen -free hydrogen -free hydrogen storage alloy, reduce production costs, and achieve efficient and economical hydrogen storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004114783850000081
    Figure BDA0004114783850000081
  • Figure BDA0004114783850000091
    Figure BDA0004114783850000091
Patent Text Reader

Abstract

The present invention provides a vanadium-free hydrogen storage alloy and a preparation method thereof, wherein the preparation method comprises the following steps: (1) metal Ti, metal Cr and metal M are mixed and smelted to obtain a cast alloy; (2) the cast alloy obtained in step (1) is subjected to melt rapid quenching to obtain the vanadium-free hydrogen storage alloy; in step (1), the molar ratio of the metal Ti, metal Cr and metal M is (4-5):(5-6):(0.1-0.5); in step (1), the metal M comprises any one of Mo, Nb or W or a combination of at least two thereof. The present invention realizes phase regulation by melt rapid quenching to obtain a vanadium-free hydrogen storage alloy having a BCC structure, and optimizes the raw material composition to improve the capacity and hydrogen absorption and desorption performance of the obtained vanadium-free hydrogen storage alloy; the preparation method is simple, low-cost and easy to promote.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of alloy technology preparation, and relates to a hydrogen storage alloy and a preparation method thereof, and in particular to a vanadium-free hydrogen storage alloy and a preparation method thereof. Background Art

[0002] As a renewable clean energy, hydrogen energy has broad application prospects. With the increasing shortage of petrochemical energy and the increasingly serious environmental pollution, hydrogen energy has received more and more attention. Fuel cells using hydrogen as fuel have been gradually applied in fields such as hydrogen-fueled cars, mopeds, motorcycles, etc. However, its hydrogen source supply system, that is, the storage and transportation of hydrogen, is currently one of the bottlenecks restricting the further application of hydrogen energy. How to properly solve this problem has become an urgent task.

[0003] Traditional hydrogen storage methods are divided into high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage and solid-state hydrogen storage. Among them, solid-state hydrogen storage has a high hydrogen storage capacity, does not require high-pressure or heat-insulated containers, and has no explosion risk. It is an ideal hydrogen storage method. Solid-state hydrogen storage materials mainly include hydrogen storage alloys, nanomaterials and graphene materials. Hydrogen storage alloys have attracted much attention due to their mild working conditions. CN102443730B discloses a hydrogen storage alloy, which is a high entropy alloy and has Co u Fe v Mn w Ti x V y Zr z The hydrogen storage alloy provided by this technical solution is an alloy material without rare earth elements, has a single C14Laves phase structure, has a stable structure, can have high hydrogen absorption / desorption capacity and hydrogen storage capacity at room temperature under normal temperature and pressure working conditions, can be widely used in hydrogen storage, heat storage, heat pumping, hydrogen purification and isotope separation, as well as in the fields of secondary batteries and fuel cells, and will not produce polluting gases that are harmful to the earth. It is a green and environmentally friendly energy with great development potential.

[0004] CN101532102B discloses a rare earth hydrogen storage alloy, the chemical formula of which has the following general formula: 1-x Dy x (Ni a Co b Al c Mn d Cu e Fe f Sn g Cr h Zn i), where 0<x<0.3, 2<a<4, 0<b<0.3, 0.2<c<0.4, 0.2<d<0.5, 0<e<0.2, 0<f<0.25, 0<g<0.22, 0≤h<0.18, 0<i<0.28, Ml is a mixed rare earth. This technical solution uses Cu, Cr, Zn, Fe, Sn to replace the Co element in the rare earth hydrogen storage alloy, which can significantly improve the cycle stability of the hydrogen storage alloy, and is comparable to the commercial hydrogen storage alloy MlNi 3.55 Co 0.75 Mn 0.4 Al 0.3 In comparison, the Co content in the hydrogen storage alloy is reduced by more than 60%, which greatly reduces the production cost. However, the capacity of the resulting rare earth alloy is small and cannot meet the demand for high capacity, and there is a problem of large unit cell volume expansion during the hydrogen absorption and desorption cycle.

[0005] Vanadium is the only metal element in the periodic table that can reversibly absorb and release hydrogen at room temperature and pressure. Vanadium has a body-centered cubic (BCC) structure and has a high hydrogen storage capacity. Its theoretical hydrogen storage capacity can reach 3.8wt%. CN1207412C discloses a Ti-V based BCC phase hydrogen storage alloy with high hydrogen storage capacity. The hydrogen storage alloy composition is Ti 100-x-y-z V x Mn y M z , where 15≤x≤50, 5≤y≤30, 5≤z≤30, 50≤x+y+z≤80 (x, y, z are all atomic percentages). M is at least one or two elements selected from Cr, Fe, Ni or RE (rare earth). The alloy forms a single BCC solid solution phase or a two-phase structure in which the BCC phase contains part of the C14Laves phase. The production of the alloy includes an annealing process, and the conditions are: annealing at 800-1500℃ for 0.5-50h. The maximum hydrogen content of the alloy is 3.8-4.2%, and the hydrogen release below 100℃ is 2.5-3%. However, vanadium has the disadvantage of being expensive as a raw material for hydrogen storage alloys.

[0006] On the basis that the vanadium-based hydrogen storage alloy has a BCC structure, the present invention proposes a vanadium-free hydrogen storage alloy with a BCC structure, optimizes the hydrogen storage performance of the obtained hydrogen storage alloy through lattice regulation and melt rapid quenching, and reduces the hydrogen storage cost of the alloy. Summary of the invention

[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a vanadium-free hydrogen storage alloy and a preparation method thereof, and through the optimized design of raw material components and phase regulation, the capacity and hydrogen storage performance of the hydrogen storage alloy are improved and the production cost is reduced.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a vanadium-free hydrogen storage alloy, the preparation method comprising the following steps:

[0010] (1) Metal Ti, metal Cr and metal M are mixed and smelted to obtain a cast alloy;

[0011] (2) subjecting the cast alloy obtained in step (1) to rapid quenching of the melt to obtain the vanadium-free hydrogen storage alloy;

[0012] The molar ratio of metal Ti, metal Cr and metal M in step (1) is (4-5):(5-6):(0.1-0.5);

[0013] The metal M in step (1) includes any one of Mo, Nb or W, or a combination of at least two of them.

[0014] The preparation method provided by the present invention optimizes the raw material composition and realizes phase regulation by rapid quenching of the melt, thereby improving the capacity and hydrogen absorption and desorption performance of the obtained vanadium-free hydrogen storage alloy; the preparation method is simple, low-cost and easy to promote.

[0015] The metal Ti described in the present invention is Ti alone; the metal Cr described is Cr alone; and the metal M described is M alone.

[0016] In the step (1) of the present invention, the molar ratio of metal Ti, metal Cr and metal M is (4-5): (5-6): (0.1-0.5), for example, it can be 4:5:0.1, 4.5:5.5:0.3, 5:6:0.5, 4:6:0.1 or 5:5:0.1, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. In the process of preparing the hydrogen storage alloy, the present invention optimizes the raw material components of metal Ti, metal Cr and metal M to improve the hydrogen storage performance of the obtained hydrogen storage alloy.

[0017] In the raw material components of the present invention, when the content of metal Ti is too low, the lattice constant of the obtained vanadium-free hydrogen storage alloy is too small, which reduces the hydrogen absorption amount and affects the hydrogen storage performance; when the Ti content is too high, the lattice constant of the obtained hydrogen storage alloy is too large, the hydrogen absorption amount is slightly increased, but the platform pressure is low, resulting in a decrease in the effective hydrogen release amount, which also affects the hydrogen storage performance.

[0018] The metal M in step (1) includes any one of Mo, Nb or W or a combination of at least two of them. Typical but non-limiting combinations include a combination of Mo and Nb, a combination of Mo and W, a combination of Nb and W, or a combination of Mo, Nb and W.

[0019] For example, when M is Mo, if the Mo content is too low, the hydrogen absorption and desorption platform pressure of the vanadium-free hydrogen storage alloy will be too low and hydrogen cannot be effectively desorbed; if the Mo content is too high, due to the high melting point of Mo and the large difference in melting point between Mo and Ti and Cr, the high Mo content will cause the vanadium-free hydrogen storage alloy to produce greater stress during the rapid quenching of the melt, resulting in a larger slope of the hydrogen absorption and desorption platform and reducing the amount of hydrogen absorption.

[0020] When M is Nb, if the Nb content is too low, the vanadium-free hydrogen storage alloy cannot form a single BCC phase, resulting in a reduction in the theoretical hydrogen storage sites; if the Nb content is too high, the lattice constant of the resulting vanadium-free hydrogen storage alloy is too high, resulting in a decrease in the hydrogen absorption and desorption platform, thereby reducing the effective hydrogen release and affecting the hydrogen storage performance.

[0021] When M is W, if the W content is too low, the vanadium-free hydrogen storage alloy will not be able to form a single BCC phase, resulting in a reduction in theoretical hydrogen storage sites; if the W content is too high, due to the high melting point of W, the components will be unevenly distributed and metal element compounds will be formed, resulting in a reduction in hydrogen storage sites.

[0022] Preferably, the smelting current in step (1) is 100-200A, for example, 100A, 120A, 140A, 160A, 180A or 200A, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0023] Preferably, the smelting in step (1) is performed 3-5 times, for example, 3 times, 4 times or 5 times.

[0024] Preferably, the smelting time in step (1) is 10-25 s / time, for example, it can be 10 s / time, 12 s / time, 14 s / time, 16 s / time, 18 s / time or 20 s / time, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] Preferably, the crystal structure of the cast alloy obtained in step (1) is Laves phase.

[0026] Preferably, the lattice constant a of the cast alloy obtained in step (1) is 0.68-0.7 nm, for example, 0.68 nm, 0.69 nm or 0.7 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0027] Preferably, the induction melting power of the rapid quenching of the melt in step (2) is 10-20 kW, for example, 10 kW, 12 kW, 14 kW, 16 kW, 18 kW or 20 kW, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the time for rapid quenching the melt in step (2) is 3-10 min, for example, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] Preferably, the speed of rapid quenching of the melt in step (2) is 5-20 m / s, for example, 5 m / s, 8 m / s, 10 m / s, 13 m / s, 15 m / s, 18 m / s or 20 m / s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0030] Preferably, the crystal structure of the vanadium-free hydrogen storage alloy obtained in step (2) is a BCC phase.

[0031] Preferably, the lattice constant of the vanadium-free hydrogen storage alloy obtained in step (2) is 0.304-0.307 nm, for example, 0.304 nm, 0.305 nm, 0.306 nm or 0.307 nm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] As a preferred technical solution of the preparation method described in the first aspect of the present invention, the preparation method comprises the following steps:

[0033] (1) After mixing metal Ti, metal Cr and metal M, smelting them 3-5 times at a current of 100-200 A for 10-25 s / time to obtain a cast alloy having a Laves phase crystal structure; the lattice constant a of the obtained cast alloy is 0.68-0.7 nm;

[0034] (2) the cast alloy obtained in step (1) is subjected to melt rapid quenching at an induction melting power of 10-20 kW for 3-10 min at a melt rapid quenching speed of 5-20 m / s to obtain a vanadium-free hydrogen storage alloy having a BCC phase crystal structure; the lattice constant a of the obtained vanadium-free hydrogen storage alloy is 0.304-0.307 nm;

[0035] The molar ratio of metal Ti, metal Cr and metal M in step (1) is (4-5):(5-6):(0.1-0.5);

[0036] The metal M in step (1) includes any one of Mo, Nb or W, or a combination of at least two of them.

[0037] In a second aspect, the present invention provides a vanadium-free hydrogen storage alloy, wherein the vanadium-free hydrogen storage alloy is obtained by the preparation method described in the first aspect.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The metal M in the present invention is Mo, Nb or W with a BCC structure, and phase regulation is achieved through rapid quenching of the melt to obtain a vanadium-free hydrogen storage alloy with a BCC structure, and the raw material composition is optimized to improve the capacity and hydrogen absorption and desorption performance of the obtained vanadium-free hydrogen storage alloy; the preparation method is simple, low in cost and easy to promote. DETAILED DESCRIPTION

[0040] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0041] Example 1

[0042] This embodiment provides a method for preparing a vanadium-free hydrogen storage alloy, the preparation method comprising the following steps:

[0043] (1) mixing metal Ti, metal Cr and metal M, wherein the molar ratio of metal Ti, metal Cr and metal M is 4.5:5.3:0.2; melting them in an electric arc furnace at a current of 150 A and a vacuum of 400 Pa for 4 times, with a melting time of 20 s / time, to obtain a cast alloy;

[0044] The metal M is Mo;

[0045] (2) The cast alloy obtained in step (1) is subjected to melt rapid quenching at an induction melting power of 15 kW for 4 minutes at a melt rapid quenching speed of 10 m / s to obtain the vanadium-free hydrogen storage alloy.

[0046] Example 2

[0047] This embodiment provides a method for preparing a vanadium-free hydrogen storage alloy, the preparation method comprising the following steps:

[0048] (1) mixing metal Ti, metal Cr and metal M, wherein the molar ratio of metal Ti, metal Cr and metal M is 4:6:0.2, and smelting them three times in an electric arc furnace at a current of 100 A and a vacuum degree of 300 Pa, with a smelting time of 25 s / time, to obtain a cast alloy;

[0049] The metal M is Nb;

[0050] (2) The cast alloy obtained in step (1) is subjected to melt rapid quenching at an induction melting power of 10 kW for 10 minutes at a melt rapid quenching speed of 5 m / s to obtain the vanadium-free hydrogen storage alloy.

[0051] Example 3

[0052] This embodiment provides a method for preparing a vanadium-free hydrogen storage alloy, the preparation method comprising the following steps:

[0053] (1) mixing metal Ti, metal Cr and metal M, wherein the molar ratio of metal Ti, metal Cr and metal M is 5:5:0.1, and smelting them five times in an electric arc furnace at a current of 200 A and a vacuum degree of 500 Pa, with the smelting time being 10 s / time, to obtain a cast alloy;

[0054] The metal M is W;

[0055] (2) The cast alloy obtained in step (1) is subjected to melt rapid quenching at an induction melting power of 20 kW for 3 minutes at a melt rapid quenching speed of 20 m / s to obtain the vanadium-free hydrogen storage alloy.

[0056] Example 4

[0057] This embodiment provides a method for preparing a vanadium-free hydrogen storage alloy. In the preparation method, except that the induction melting power of the melt rapid quenching in step (2) is 18 kW and the time of the melt rapid quenching is 3 minutes, the rest is the same as that of Example 1.

[0058] Example 5

[0059] This embodiment provides a method for preparing a vanadium-free hydrogen storage alloy. In the preparation method, except that the induction melting power of the melt rapid quenching in step (2) is 20 kW and the speed of the melt rapid quenching is 15 m / s, the rest is the same as that of Example 4.

[0060] Comparative Example 1

[0061] This comparative example provides a method for preparing a cast alloy. In the preparation method, except that the cast alloy obtained in step (1) is not subjected to melt rapid quenching, the rest is the same as that of Example 1.

[0062] Comparative Example 2

[0063] This comparative example provides a method for preparing a vanadium-free hydrogen storage alloy. In the preparation method, except that the molar ratio of metal Ti, metal Cr and metal M in step (1) is 6:3.8:0.2, the rest is the same as Example 1.

[0064] Comparative Example 3

[0065] This comparative example provides a method for preparing a vanadium-free hydrogen storage alloy. In the preparation method, except that the molar ratio of metal Ti, metal Cr and metal M in step (1) is 3.8:6:0.2, the rest is the same as Example 1.

[0066] Comparative Example 4

[0067] This comparative example provides a method for preparing a vanadium-free hydrogen storage alloy. In the preparation method, except that the molar ratio of metal Ti, metal Cr and metal M in step (1) is 4:4:2, the rest is the same as that in Example 1.

[0068] Comparative Example 5

[0069] This comparative example provides a method for preparing a vanadium-free hydrogen storage alloy. In the preparation method, except that the molar ratio of metal Ti, metal Cr and metal M in step (1) is 4.5:5.45:0.05, the rest is the same as Example 1.

[0070] Performance Testing

[0071] The performance tests were carried out on the vanadium-free hydrogen storage alloys obtained in Examples 1-5 and Comparative Examples 2-5, and the cast alloy obtained in Comparative Example 1. The physical phases of the cast alloys and the vanadium-free hydrogen storage alloys obtained in the preparation process were tested by XRD. The maximum hydrogen absorption capacity, effective hydrogen desorption capacity and platform pressure of the vanadium-free hydrogen storage alloys obtained in Examples 1-5 and Comparative Examples 2-6, and the cast alloy obtained in Comparative Example 1 were tested under the conditions of H2 pressure of 8 MPa and temperature of 25°C. The specific testing methods refer to the national standard GB / T 33291-2016.

[0072] The results are shown in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] It can be seen from Examples 1-5 that in the preparation method provided by the present invention, the phase transformation of the crystal structure from Laves to BCC is achieved by the method of rapid quenching of the melt, and the obtained vanadium-free hydrogen storage alloy has excellent hydrogen storage performance, with a maximum hydrogen absorption capacity of up to 3.6wt%, an effective hydrogen release capacity of up to 2.3wt%, and a platform pressure of about 0.2MPa.

[0077] From the comparison between Comparative Example 1 and Example 1, it can be seen that the hydrogen storage performance of the cast alloy without melt rapid quenching is slightly lower than that of the vanadium-free hydrogen storage alloy, the maximum hydrogen absorption capacity is only 1.8wt%, the effective hydrogen release capacity is only 0.7wt%, and the hydrogen absorption and release platform is relatively inclined without platform pressure.

[0078] From the comparison between Comparative Examples 2 and 3 and Example 1, it can be seen that in the process of preparing the hydrogen storage alloy, the present invention optimizes the raw material components of metal Ti, metal Cr and metal M, so that the cast alloy obtained in step (1) undergoes a phase transformation, thereby improving the hydrogen storage performance of the obtained hydrogen storage alloy. When the Ti content is too high, the lattice constant of the obtained hydrogen storage alloy is greater than 0.307nm, and the hydrogen absorption amount is slightly increased, but the platform pressure is low, resulting in a decrease in the effective hydrogen release amount, which also affects the hydrogen storage performance; when the Ti content is too low, the lattice constant of the obtained vanadium-free hydrogen storage alloy is less than 0.304nm, which reduces the hydrogen absorption amount and cannot form a single BCC phase, affecting the hydrogen storage performance.

[0079] From the comparison between Comparative Examples 4-5 and Example 1, it can be seen that in the process of preparing the hydrogen storage alloy, the present invention optimizes the raw material components of metal Ti, metal Cr and metal M, so that the cast alloy obtained in step (1) undergoes a phase transformation, thereby improving the hydrogen storage performance of the obtained hydrogen storage alloy. When the content of Mo is too high, due to the high melting point of Mo and the large difference in melting point between Mo and Ti and Cr, the excessively high Mo content will cause the vanadium-free hydrogen storage alloy to generate greater stress during the rapid quenching of the melt, resulting in a larger slope of the hydrogen absorption and desorption platform, thereby reducing the amount of hydrogen absorption; when the content of Mo is too low, the alloy hydrogen absorption and desorption platform is low and hydrogen cannot be effectively desorbed.

[0080] In summary, the present invention provides a vanadium-free hydrogen storage alloy and a preparation method thereof, wherein the metal element M is Mo, Nb or W having a BCC structure, and phase regulation is achieved by rapid quenching of the melt to obtain a vanadium-free hydrogen storage alloy having a BCC structure, and the raw material composition is optimized to improve the capacity and hydrogen absorption and desorption performance of the obtained vanadium-free hydrogen storage alloy; the preparation method is simple, low-cost, and easy to promote.

[0081] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a vanadium-free hydrogen storage alloy, characterized in that: The preparation method comprises the following steps: (1) Metal Ti, metal Cr and metal M are mixed and smelted to obtain a cast alloy; (2) subjecting the cast alloy obtained in step (1) to rapid quenching of the melt to obtain the vanadium-free hydrogen storage alloy; The molar ratio of metal Ti, metal Cr and metal M in step (1) is (4-5):(5-6):(0.1-0.5); The metal M in step (1) includes any one of Mo, Nb or W, or a combination of at least two thereof; The crystal structure of the vanadium-free hydrogen storage alloy obtained in step (2) is a BCC phase; The lattice constant a of the vanadium-free hydrogen storage alloy obtained in step (2) is 0.304-0.307nm.

2. The preparation method according to claim 1, characterized in that: The smelting current in step (1) is 100-200A.

3. The preparation method according to claim 1, characterized in that: The smelting is performed 3-5 times in step (1).

4. The preparation method according to claim 1, characterized in that: The smelting time in step (1) is 10-25s / time.

5. The preparation method according to claim 1, characterized in that: The crystal structure of the cast alloy obtained in step (1) is Laves phase.

6. The preparation method according to claim 5, characterized in that: The lattice constant a of the cast alloy obtained in step (1) is 0.68-0.7nm.

7. The preparation method according to claim 1, characterized in that: The induction melting power of the rapid quenching of the melt in step (2) is 10-20kW.

8. The preparation method according to claim 1, characterized in that: The time for rapid quenching of the melt in step (2) is 3-10 minutes.

9. The preparation method according to claim 1, characterized in that: The speed of the melt rapid quenching in step (2) is 5-20m / s.

10. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) After mixing metal Ti, metal Cr and metal M, smelting them 3-5 times at a current of 100-200 A for 10-25 s / time to obtain a cast alloy having a Laves phase crystal structure; the lattice constant a of the obtained cast alloy is 0.68-0.7 nm; (2) the cast alloy obtained in step (1) is subjected to melt rapid quenching at an induction melting power of 10-20 kW for 3-10 min at a melt rapid quenching speed of 5-20 m / s to obtain a vanadium-free hydrogen storage alloy having a BCC phase crystal structure; the lattice constant a of the obtained vanadium-free hydrogen storage alloy is 0.304-0.307 nm; The molar ratio of metal Ti, metal Cr and metal M in step (1) is (4-5):(5-6):(0.1-0.5); The metal M in step (1) includes any one of Mo, Nb or W, or a combination of at least two of them.

11. A vanadium-free hydrogen storage alloy, characterized in that: The vanadium-free hydrogen storage alloy is obtained by the preparation method according to any one of claims 1-10.

Citation Information

Patent Citations

  • Rare-earth series hydrogen storage alloy

    CN101532102B

  • Hydrogen storage alloy

    CN102443730B

  • METHOD FOR PRODUCING Ti-Nb-Cr HYDROGEN STORAGE ALLOY BYMELT SPINNING

    KR100712687B1

  • Hydrogen storage alloy

    US20030003010A1